Molecular screening of anti-quorum sensing capability of Salvadora persica on Enterococcus faecalis - Rezaei, Afsaneh (Animo Repository, 2011)
Quorum sensing (QS) refers to the phenomenon characterized by the accumulation of signaling molecules enabling a cell to sense a bacterial population triggering a coordinated response. Enterococcus faecalis is a resistant microorganism commonly found in oral infections. Salvadora persica has been traditionally used in Middle East countries to clean the teeth due to its antimicrobial activity. The study investigated the anti-quorum sensing (AQS) ability of S. persica extracts on E. faecalis. Extracts from the bark, leaves, root and shoots were tested against Chromobacterium violaceum. AQS ability was determined using differential scanning fluorimetry (DSF) and elastolytic assay to detect the level of protease and quantitative polymerase chain reaction (QPCR) to detect cytolysin (cylR1) and gelatinase (gelE) virulence factors. Preliminary disk diffusion assays revealed AQS activity by inhibiting violacein pigment production in C. violaceum without affecting its growth. Furthermore, only negligible amount of proteases was detected in DSF and elastolytic assays. CylR1 and gelE gene expression revealed no detectable signals even from the lowest possible threshold. The results indicate that S. persica has AQS ability against E. faecalis. S. persica extract can be used as alternative or in combination with other anti-microbial agents against infections caused by E. faecalis. © 2010 The Hard Tissue Biology Network Association.